The Enlightenment Tradition of Nepal: Can the Civil Society Grasp it? - Dahal, Dev Raj (Dhaulagiri Journal of Sociology and Anthropology, 2014)
Nepal's history of enlightenment reflects three traditions—Vedic, Videha Janak and Buddhist. Each of these traditions searches the meaning of life, actual human condition, links with nature and ways of emancipation. The cardinal features of its native civil society are rooted into niskam karma (selfless service) to others, enlightened thinking and action. Modern civil society troubled by the turmoil of post-modernity needs to capture this ancient wisdom that sees human life in the interconnection with other species rather than isolated fragments and requires to perform many other tasks to move the this post-conflict nation from violence to stable peace. Nourishing the civic virtues of freedom, justice, solidarity, reconciliation and peace are vital nutrients. DOI: http://dx.doi.org/10.3126/dsaj.v8i0.10720 Dhaulagiri Journal of Sociology and Anthropology Vol. 8, 2014; 1-28